A hétköznapi tárgyhasználat mint kultúrafenntartó újrajátszás: Kunkovács László fotói a paraszti élet szocialista átalakulásáról - Nagy, Károly Zsolt (Studia Litteraria, 2024)
László Kunkovács’s oeuvre, which focuses on the visual documentation of the socialist transformation of the peasant way of life, is a hard-to-miss achievement in the history of Hungarian photography in the second half of the 20th century. Not only because of the undisputed social historical significance of his subjects and the documentary value of his images, but also because he built up a very specific aesthetic vision of the subject on the borders of social science and photography. Kunkovács’s most significant works are concerned with the memory of objects, the mimetic memory and its ritual dimensions, but he is most interested in their interplay and interaction. Through the photography of these aspects he demonstrates the body techniques, in the Maussian sense, of transmitting cultural or culturally fixed knowledge that are difficult to grasp in other ways. is paper views Kunkovács’s work from the perspective of the role of memory and body techniques in cultural transmission and the possibility of addressing these issues through visual anthropology.